Results of Experience Management with a Tale-Based Activity Package to Promote Morality and Ethics of Pre-School Children at Watsothonwanaram Worawiharn School - Yampeng, Ammarin; Wangkaeohiran, Thipwimol; Settacomkul, Supat (Journal of Graduate Research, 2020)
The objectives of this research were to study the pre-school children’s moral and ethical behaviors after having undergone through a tale-learning experience package to promote morality and ethics, and 2.) to explore the pre-school children’s satisfaction the experience management with the tale-based activity package to promote morality and ethics. The cluster random sampling method was applied to select 30 subjects in Kindergarten Class 1 at Watsothornwararam School in the first semester of the 2019 academic year. The research instruments consisted of the tale-based activity package, the moral and ethical behavior assessment of the children, and the questionnaire on the children’s satisfaction the experience management with the tale-based activity package. The data were statistically analyzed for percentage. The research results revealed that the children’s overall moral and ethical behaviors after having undergone through the tale-learning experience package was at a high level, and their overall satisfaction the experience management with the tale-based activity package to promote morality and ethics was at a high level; ( = 2.64, S.D. = 0.45).